Exploring the Risks and Benefits of Speculative Business From Islamic Perspectives - Abba Alhaji Bukar; Wakil Mala Bukar; Bintu Mustapha (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
This study addresses a critical gap in contemporary Islamic finance literature concerning the normative and empirical assessment of speculative business practices. While prior research predominantly adopts a prohibitive approach by equating speculation with riba, gharar, and maysir, limited attention has been given to a balanced evaluation that systematically examines both the risks and the conditional benefits of speculative activities within a Shari’ah-compliant framework. Moreover, insufficient integration exists between classical fiqh al-muʿāmalāt principles and modern speculative instruments such as derivatives, foreign exchange trading, and cryptocurrencies. The objective of this research is to critically analyze speculative business from an Islamic perspective by assessing its compatibility with the objectives of Shari’ah (maqāṣid al-sharī‘ah), particularly the protection of wealth (ḥifẓ al-māl), and by identifying its socio-economic implications. Methodologically, the study employs a qualitative survey design based on systematic desk review, synthesizing classical jurisprudential sources, Qur’anic and Hadith foundations, and contemporary empirical financial studies. Analytical triangulation is applied to examine risk origin, ethical boundaries, and practical financial structures. The findings reveal that speculative business becomes impermissible when characterized by excessive uncertainty, gambling-like behavior, and detachment from real economic activity. However, rational risk-taking linked to tangible assets, transparent contracts, and equitable profit-and-loss sharing may yield legitimate economic benefits such as market liquidity, price discovery, innovation, and capital allocation. The study further proposes Shari’ah-compliant alternatives, including mudarabah, musharakah, and asset-backed investment mechanisms, as viable substitutes for high-risk speculative models. Internationally, the research contributes to the development of ethical financial governance frameworks, offering policy-relevant insights for emerging and developed economies seeking to enhance market stability, social justice, and sustainable economic growth within Islamic and global financial systems.